Innovations in Design, Construction, and Management of Pingnan Third Bridge—The Largest-Span Arch Bridge in the World. Issue 2 (3rd April 2022) - Zheng, Jielian; Du, Hailong; Mu, Tingmin; Liu, Jiaping; Qin, Dayan; Mei, Guoxiong; Tu, Bing
Abstract: The main bridge of Pingnan Third Bridge is a half-through concrete-filled steel tubular (CFST) arch bridge with a span of 575 m, and it is the largest-span arch bridge worldwide. Several innovative technologies were proposed and adopted with respect to the design, construction and management of Pingnan Third Bridge, including: (1) integrated design and prefabricated construction technologies based on the independent cantilever unit concept to accelerate the assembly of the steel truss for the main arch; (2) a BeiDou Navigation Satellite System (BDS) based active force control and displacement adjustment technology for the construction tower and a force optimization model for the one-time tensioning of buckled cables; (3) the vacuum-assisted filling technique integrated with an advanced timed expansion and shrinkage compensation technology that generally solved the historically stubborn defect of in-tube concrete de-bonding and voiding in the CFST arch bridge industry; (4) a novel composite bridge foundation of the diaphragm wall encapsulating a grouting-reinforced pebble layer for the northern abutment of the Pingnan Third Bridge; and (5) a new management paradigm integrating informatization and intelligent technology to promote the construction management efficiency of the large-span bridge. These proposed innovative technologies can serve as good references for the construction of similar large bridges in the future.